An Ultrasoft Self‐Fused Supramolecular Polymer Hydrogel for Completely Preventing Postoperative Tissue Adhesion. Issue 16 (18th March 2021) - Yu, Jing; Wang, Ke; Fan, Chuanchuan; Zhao, Xiaoye; Gao, Jushan; Jing, Wanghui; Zhang, Xiaoping; Li, Jia; Li, Yuan; Yang, Jianhai; Liu, Wenguang
Abstract: The intermolecular H‐bonding density heavily influences the gelation and rheological behavior of hydrogen‐bonded supramolecular polymer hydrogels, thus offering a delicate pathway to tailor their physicochemical properties for meeting a specific biomedical application. Herein, one methylene spacer between two amides in the side chain of N ‐acryloyl glycinamide (NAGA) is introduced to generate a variant monomer, N ‐acryloyl alaninamide (NAAA). Polymerization of NAAA in aqueous solution affords an unprecedented ultrasoft and highly swollen supramolecular polymer hydrogel due to weakened H‐bonds caused by an extra methylene spacer, which is verified by variable‐temperature Fourier transform infrared (FTIR) spectroscopy and simulation calculation. Intriguingly, poly( N ‐acryloyl alaninamide) (PNAAA) hydrogel can be tuned to form a transient network with a self‐fused and excellent antifouling capability that results from the weakened dual amide H‐bonding interactions and enhanced water‐amide H‐bonding interactions. This self‐fused PNAAA hydrogel can completely inhibit postoperative abdominal adhesion and recurrent adhesion after adhesiolysis in vivo. This transient hydrogel network allows for its disintegration and excretion from the body. The molecular mechanism studies reveal the signal pathway of PNAAA hydrogel in inhibiting inflammatory response and regulating fibrinolytic system balance. This self‐fused, antifouling ultrasoft supramolecular hydrogel is promising as a barrier biomaterial for completely preventing postoperative tissue adhesion. Abstract : One more methylene makes a difference: introducing one extra methylene between two amides in the side chain of poly( N ‐acryloyl alaninamide) weakens the H‐bonding interaction, resulting in an ultrasoft and highly swollen supramolecular polymer hydrogel that can be tuned to form a transient network with a self‐fused and antifouling ability, which is harnessed to completely prevent postoperative tissue adhesion.